Do nurses document all discussions of patient problems and nursing interventions in the electronic health record? A pilot study in home healthcare. Issue 2 (26th May 2022) - Song, Jiyoun; Zolnoori, Maryam; Scharp, Danielle; Vergez, Sasha; McDonald, Margaret V; Sridharan, Sridevi; Kostic, Zoran; Topaz, Maxim
Abstract: Objective: To assess the overlap of information between electronic health record (EHR) and patient–nurse verbal communication in home healthcare (HHC). Methods: Patient–nurse verbal communications during home visits were recorded between February 16, 2021 and September 2, 2021 with patients being served in an organization located in the Northeast United States. Twenty-two audio recordings for 15 patients were transcribed. To compare overlap of information, manual annotations of problems and interventions were made on transcriptions as well as information from EHR including structured data and clinical notes corresponding to HHC visits. Results: About 30% (1534/5118) of utterances (ie, spoken language preceding/following silence or a change of speaker) were identified as including problems or interventions. A total of 216 problems and 492 interventions were identified through verbal communication among all the patients in the study. Approximately 50.5% of the problems and 20.8% of the interventions discussed during the verbal communication were not documented in the EHR. Preliminary results showed that statistical differences between racial groups were observed in a comparison of problems and interventions. Discussion: This study was the first to investigate the extent that problems and interventions were mentioned in patient–nurse verbal communication during HHC visits and whether this information was documented in EHR. Our analysis identified gaps in information overlap and possible racial disparities. Conclusion: Our results highlight the value of analyzing communications between HHC patients and nurses. Future studies should explore ways to capture information in verbal communication using automated speech recognition. Lay Summary: During home healthcare (HHC) visits, nurses are actively engaged in verbal communication with their patients, and they document information in electronic health records (EHRs) based on verbal communication with patients and objective observations. However, not all obtained information may be documented in the EHR. Thus, this study aimed to assess the overlap of information between EHR and patient–nurse verbal communication in HHC. We recorded patient–nurse verbal communications during HHC visits in one of the largest HHC organizations in the Northeast Unites States. Among those, 22 audio recordings for 15 patients were transcribed for analysis. To compare the overlap of information, transcriptions, as well as EHR data corresponding to HHC visits, were annotated manually for problems and interventions. About 30% of utterances (ie, spoken language preceding/following silence or a change of speaker) were identified as including problems or interventions. Approximately 50.5% of the problems and 20.8% of the interventions discussed during the verbal communication were not documented in the EHR. Preliminary results showed that statistical differences between racial groups were observed in a comparison of problems and interventions. An identified gap in information overlap and racial disparities highlighted the value of analyzing verbal communications between patients and nurses in HHC.